(untitled) (World of finance, 2019)
Introduction. Today, due to the large number of types of intangible assets that are presented in the valuation and accounting standards of different levels, it is difficult to determine their objective assessments. Purpose. The article is devoted to the research and systematization of IA objects, presented in the international, European and national standards of expert assessment and accounting, with the aim to find the ways of domestic standards improvement, as well as management of IA at the enterprise. Results. The structure of the IA objects, which are described in the International Standard for Assessments 210 “Intangible Assets”, the European Standards for Evaluation of the TEGoVA, the Professional Standards for the Evaluation of RICS, the National Standard No. 4 “Appraisal of Intellectual Property Rights”, the International Accounting Standard 38, Intangible Assets, and the Standards of Accounting 8 “Intangible Assets”, is analyzed. It is established that the objects of IA are shown in the international and national accounting standards, which are reflected in the accounting and financial statements of the entity, but they do not fully cover the market value of the enterprise. The list of objects of IA, which is not given in P (C) BO 8, is marked out and described, and accordingly they are not reflected in the financial statements of the enterprise. The article proposes a list of IA, which was formed on the basis of study of the nternational, European and national standards of expert assessment and can be taken into account by the enterprise for the estimation of business value and needs of IAmanagement. Conclusions. It is noted that the assessment of IA is not a sufficiently developed direction of professional property valuation; therefore, there is a need to mprove the National Standard 4 “Appraisal of Intellectual Property Rights” from its approximation to international practice. It has been determined that a standard for the assessment of IA, which will regulate not only the evaluation of intellectual property objects, but also other IA objects, which will be used in international practice, taking into account contemporary economic development, will be developed. The results of this article outlined the directions of further research in the area of improving the methodology of IA assessment.